2014
DOI: 10.1123/ijsnem.2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating and Eating Disorders in Aquatic Sports

Abstract: Disordered eating behavior (DE) and eating disorders (EDs) are of great concern because of their associations with physical and mental health risks and, in the case of athletes, impaired performance. The syndrome originally known as the Female Athlete Triad, which focused on the interaction of energy availability, reproductive function, and bone health in female athletes, has recently been expanded to recognize that Relative Energy Deficiency in Sport (RED-S) has a broader range of negative effects on body sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
0
18
0
4
Order By: Relevance
“…PAR = physical activity record. bolic rate, hormonal disturbances, menstrual dysfunction, suboptimal bone health, and an increased risk of illness and injury Melin et al, 2014). Recently, a study highlighted the impact of a low energy availability specifically on swimmers (VanHeest et al, 2014).…”
Section: Energy Requirements=mentioning
confidence: 99%
See 1 more Smart Citation
“…PAR = physical activity record. bolic rate, hormonal disturbances, menstrual dysfunction, suboptimal bone health, and an increased risk of illness and injury Melin et al, 2014). Recently, a study highlighted the impact of a low energy availability specifically on swimmers (VanHeest et al, 2014).…”
Section: Energy Requirements=mentioning
confidence: 99%
“…These populations should be targeted for sound professional advice regarding the setting and achievement of long-term goals for ideal physique. The problem of disordered eating and eating disorders within aquatic sports is covered in more detail by Melin et al (2014).…”
Section: Physique and Performance In Swimmingmentioning
confidence: 99%
“…Occasionally, the high training volume results in below adequate energy intake for the swimmer to maintain adequate energy balance, with intake that can reach the 2400 kcal/day on extreme training periods 15 . It is worth mentioning here, that energy deficits maintained for long periods of time, could result in decreased basal metabolic rate, cause alterations in hormonal functions, disrupt menstrual cycles in women, as well as increase the risk of injury and disease 16 , 17 . It has recently been found that high level female swimmers who experience menstrual dysfunctions show a decrease in thyroid hormones and growth factors, coupled with a decrease in speed in the 400-m test after a 12-week training period 18 .…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Melin et al 26 , o comportamento alimentar do tipo restritivo pode ter estreita relação com o desempenho esportivo, corroborando os achados do bloco 1 do primeiro e segundo modelo de regressão hierárquica. Os resultados apontaram que 13% e 10% da variância do desempenho nas provas dos 100m e 200m livre, respectivamente, foi explicada pela subescala "Dieta" do EAT-26.…”
Section: Discussionunclassified